Nilai Religi dalam Novel Pijaki Langit, Mengetuk Pintu Surga Karya Novelyzius - Amanda, Wahida Nur; Deliani, Susy; Nurhayati, Nurhayati (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The purpose of this research is to know: 1. Describing the religious values contained in the novel Pijaki Langit, Mengetuk Pintu Surga Karya Novelyzius. 2. Describing the main character in the novel Pijaki Langit, Mengetuk Pintu Surga Karya Novelyzius. 3. Describing the social life of the main character in the novel Pijaki Langit Mengetuk Pintu Surga Karya Novelyzius. In this study, the author used descriptive qualitative research to analyze the religious value contained in the novel Pijaki Langit Mengetuk Pintu Heaven Karya Novelyzius, analyze the character of the main character contained in the novel Pijaki Langit Mengetuk Pintu Heaven Karya Novelyzius and analyze the social life of the main character in the novel Pijaki Langit Mengetuk Pintu Heaven Karya Novelyzius. Because the purpose of qualitative research is to make descriptions, pictures or paintings that are carried out systematically, factually and accurately regarding the facts, characteristics and relationships between the phenomena investigated in accordance with the focus and objectives of the research. From the results of the research, the author can conclude that the religious values contained in the novel Pijaki Langit Mengetuk Pintu Surga by Novelyzius are as follows: 1 Religious values are the value of faith in God, the value of worship in the form of prayer, and the value of morals in the form of patience. . Religious values in the form of human relationships with God, namely gratitude to God, faith in God, religious feelings, praying or asking God. Human relations with humans, namely helping attitudes, loving attitudes towards other fellow humans. The last is the relationship between humans and themselves, namely being patient, forgiving everything that is wrong, daring to fight evil, promising or trusting to keep what has been entrusted to us and carrying out the best possible task for what has been entrusted to us.